Analysis of Leukocyte Count in Patients Acute Coronary Syndrome with ST-Segment Elevation and Acute Coronary Syndrome without ST-Segment Elevation at Kendari City General Hospital - Jamaluddin Jamaluddin; Irawaty Irawaty; Fercee Primula (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2022)
Background: Acute coronary syndrome (ACS) is an acute complication of coronary heart disease due to rupture of an atherosclerotic plaque, resulting in the formation of a thrombus, narrowing the lumen, resulting in impaired blood supply and decreased strength of heart muscle contraction. The occurrence of inflammation in the atherosclerotic process is characterized by an increase in the number of leukocytes, which causes increased leukocyte recruitment at the site of plaque rupture and is thought to play an important role in the incidence and prognosis of ACS. Purpose: The aim of this study was to determine the comparison of the number of leukocytes in STE and NSTE ACS patients. Methods: This research was an observational analytic study. The research design used a cross sectional study carried out at the Kendari City Regional General Hospital with the independent variable STE and Non STE ACS and the dependent variable was the leukocytes count. The number of samples was 73 patients. Data were collected from medical record data in accordance with the inclusion criteria.  Bivariate analysis to compare the number of leukocytes using the unpaired T test. Results: Research from 73 respondents found that STE ACS patients had a mean leucocyte count of 10.31±3.50x103/μL while NSTE ACS patients had a mean leukocyte count of 8.62±3.43 x 103/μL (p=0,000). Conclusion: There was a significant difference of leukocyte count in STE ACS and NSTE ACS patients.